Relationship between epicardial adipose tissue thickness and coronary thrombus burden in patients with ST-elevation myocardial infarction - Uslu, Abdulkadir; Kup, Ayhan; Dogan, Cem; Sari, Munevver; Cersit, Sinan; Aksu, Ugur; Kanat, Selcuk; Demir, Mehmet; Tenekecioglu, Erhan (Biomedical papers, 2020)
Background: Epicardial fat reflects abdominal visceral adiposity and visceral fat plays an important role in the development of an unfavorable metabolic and atherosclerosis risk profile. Intracoronary thrombus burden is an important factor affecting the success of the procedure particularly in patients undergoing percutaneous coronary intervention (PCI). Therefore, determining the factors predicting thrombus burden has great importance in predicting adverse cardiovascular events as well as determining the most appropriate treatment strategy to prevent failure in PCI. Aim: The aim of the current study was to evaluate the relationship between Epicardial adipose thickness (EAT) and thrombus burden in the patients with ST-elevation myocardial infarction (STEMI) who undergo primary PCI (pPCI). Methods: The study was prospective and included patients (n=156) who were referred to Kosuyolu Research and Education hospital with STEMI between 2016 and 2017. Thrombus burden was scored as follows: 0 (no thrombus), 1 (possible thrombus), 2 (definite thrombus <0.5xreference vessel diameter), 3 (definite thrombus 0.5-2xreference vessel diameter), 4 (definite thrombus >2xreference vessel diameter), and 5 (complete vessel occlusion). According to thrombus grade the patients were grouped as low thrombus burden (grades 0-3) and high thrombus burden (grades 4 and 5). EAT, identified as an echo-free space between the myocardium and visceral pericardium, was measured perpendicularly, on the free wall of the right ventricle at both parasternal long- and short-axis views at end-diastole in three cardiac cycles. Results: Fifty-one subjects were in the low thrombus burden group and 105 in the high thrombus burden group. There were no differences in the two groups for LVEF, smoking status, family history of coronary artery disease (CAD), diabetes mellitus (DM), hypertension (HT), and hypercholesterolemia and for total cholesterol, triglyceride, GFR, LDL-C and HDL-C. In multivariate logistic regression analysis the EAT (odds ratio: 2.53, 95% CI: 1.76-3.67; p < .001) was found as an independent predictor of high thrombus burden. Conclusions: The present study showed that EAT was an independent predictor of coronary thrombus burden in STEMI.
Keywords: thrombus burden; epicardial adipose thickness; acute coronary syndrome